2015
DOI: 10.1155/2015/359275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Biodentine as an Apical Plug in Nonvital Permanent Teeth with Open Apices: An In Vitro Study

Abstract: The aim of this study was to evaluate the apical microleakage of Biodentine and MTA orthograde apical plugs and to compare the effect of thickness of these biomaterials on their sealing ability. A total of eighty maxillary anterior teeth were used. The apices were removed by cutting with a diamond disc (Jota, Germany) 2 mm from the apical root end in an attempt to standardize the working length of all specimens to 15 ± 1 mm. Both materials were placed in 1–4 mm thickness as apical plugs root canal. Root canal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 29 publications
3
29
3
1
Order By: Relevance
“…24,25 One study compared the sealing ability and marginal adaptation of 4-mm thicknesses of several bioceramics used as apical plugs and found that the sealing ability of Biodentine was equal to ProRootMTA, as found in the present study. 26 In contrast to the present study, one study reported no significant microleakage of 3-mm ProRootMTA and Biodentine apical plugs. 26 Several related studies have shown a greater sealing ability of 3-mm ProRootMTA than TotalFill BC RRM putty, 27,28 and a similar adaptation of 3-mm ProRootMTA and TotalFill BC RRM putty.…”
Section: Comparisons Among Prorootmta Totalfill Bc Rrm Paste Andcontrasting
confidence: 99%
See 1 more Smart Citation
“…24,25 One study compared the sealing ability and marginal adaptation of 4-mm thicknesses of several bioceramics used as apical plugs and found that the sealing ability of Biodentine was equal to ProRootMTA, as found in the present study. 26 In contrast to the present study, one study reported no significant microleakage of 3-mm ProRootMTA and Biodentine apical plugs. 26 Several related studies have shown a greater sealing ability of 3-mm ProRootMTA than TotalFill BC RRM putty, 27,28 and a similar adaptation of 3-mm ProRootMTA and TotalFill BC RRM putty.…”
Section: Comparisons Among Prorootmta Totalfill Bc Rrm Paste Andcontrasting
confidence: 99%
“…Comparisons among ProRootMTA, TotalFill BC RRM paste and RetroMTA at 3‐mm thicknesses indicated inferior sealing ability and marginal adaptation in the present study, which is similar to results in other studies . One study compared the sealing ability and marginal adaptation of 4‐mm thicknesses of several bioceramics used as apical plugs and found that the sealing ability of Biodentine was equal to ProRootMTA, as found in the present study …”
Section: Discussionsupporting
confidence: 80%
“…Biodentine applied as an apical plug in immature teeth has been proven to be equally effective as MTA, regardless of the plug thickness [20]. In this study the fluid filtration technique was used.…”
Section: Microleakage Studiesmentioning
confidence: 99%
“…Due to their proper biological and physical characteristics, they may be successfully used as root repair materials in procedures such as retrograde obturation after a root resection [5,24,35], open apices management with an apical plug [20,22] or root perforation repair [21,33]. Thanks to the excellent biocompatibility and bioactivity, they may also be used in vital pulp therapy in endodontic procedures, such as indirect pulp capping or pulpotomy.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Biodentine is a fast‐setting (~10–12 min) calcium silicate‐based material. Several in vitro studies and case reports have recommended the use of Biodentine as an alternative to MTA due to its similar sealing ability, biocompatibility, the formation of mineralized tissue, superior hydroxyapatite apposition when exposed to tissue fluids and stimulating healing ability of periapical tissue (Bani, Sungurtekin‐Ekçi, & Odabaş, ). However, it has low radiopacity (Kaup, Schäfer, & Dammaschke, ).…”
Section: Introductionmentioning
confidence: 99%